Humanizing flies with transgenic nephrin - Simons, Matias (Kidney international, 2025)
Congenital nephrotic syndrome of the Finnish type is caused by pathogenic variants in NPHS1 encoding for nephrin. Assessing pathogenicity of genetic variants is notoriously difficult as suitable experimental models are lacking. In this issue of Kidney International, Wolff et al. report on an NPHS1 variant validation assay that is based on the formation of slit diaphragm-like structures by the overexpression of human nephrin in Drosophila nephrocytes.
Online verfügbar: 19. Juni 2025
Gesehen am 30.10.2025